Pengaruh Likuiditas, Suku Bunga dan Pertumbuhan Perusahaan Terhadap Profitabilitas pada Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2022-2024 - Zilfi Syabrina; Umi Rahma Dhany; Mutimmah Rustianawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study was carried out on banks that were listed between 2022-2024 on the Indonesia Stock Exchange (IDX). This study's primary goal is to examine how liquidity, interest rates, and company growth affect profitability. There are independent and dependent variables in this quantitative study design. to use the Purposive Sampling approach to collect samples. Social media, literature reviews, and recordkeeping are some of the data collection techniques. Data sources include Bank Indonesia and the Indonesia Stock Exchange. The study's findings indicate that liquidity positively affects profitability since increased liquidity translates into higher profitability. Interest rates have a negative impact on profitability, this is because the interest rate value is too high, so it has a low effect on banking profitability. While Company Growth has a negative impact on profitability. Based on these findings, Banking Companies are expected to optimize liquidity management, determine interest rate policies that are not too high so as not to reduce profitability and re-evaluate the company's growth strategy so as not to burden the bank.